ASCOGENLY: ANANAS COMOSUS ENZYME FOR DETERGEN ENVIRONMENTALY FRIENDLY - Tathya Dhiany Rahmania; Yuniar Dwi Setyaning (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Water is one of the most important resources for living organisms; therefore, its quality must be maintained. Indonesia is a maritime country where about 70% of its territory consists of sea and 30% land. The Surabaya City Environmental Service (DLH) reported that around 80% of pollutants entering the Tambak Wedi River originate from household waste. One major cause is surfactant substances from detergents that reduce water surface tension and harm aquatic life. To address this issue, we developed an innovation called Ascogenly, an eco-enzyme made from pineapple peels (Ananas comosus). This project aims to reduce organic waste while minimizing the use of environmentally harmful detergents. Ascogenly is produced by mixing eco-enzyme and baking soda in a 1:10 ratio. Experimental testing showed that fish exposed to commercial detergent X died during observation, whereas fish in the Ascogenly solution survived. These results indicate that Ascogenly is safer for aquatic ecosystems and does not disrupt oxygen circulation. Therefore, Ascogenly has potential as an environmentally friendly detergent alternative.